The search for justice : lawyers in the civil rights revolution, 1950-1975 - Hoffer, Peter Charles, 1944- (Chicago : The University of Chicago Press, 2019)
'The Search for Justice' is a study of the role of lawyers in the Civil Rights Revolution. The work focuses on school desegregation from 1950 to 1975 and includes counsel on both sides of the struggle in the courtroom and in Congress, the federal and state judges and justices, and law school constitutional authorities. Key cases include Sweatt v. Painter, Brown v. Board of Education, and NAACP v. Alabama. Key players include Thurgood Marshall, Robert L. Carter, John W. Davis, Earl Warren, James Patterson, Strom Thurmond, Richard Russell, Alexander Bickel, and Herbert Wechsler. The argument is that the outcome of the struggle was never inevitable: lawyers for segregation did an able job of representing their clients, and in some sense were successful with resegregating neighborhood schools.
Also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 22, 2019).
Keywords: Civil rights lawyers -- United States -- History -- 20th century; Law -- United States -- History -- 20th century; Civil rights -- United States -- History -- 20th century; Segregation in education -- Law and legislation -- United States; United States -- History -- 1945-; Law; Jurisprudence & general issues